SMART-HTN Pocketbook Education and Improved Medication Adherence and Blood Pressure Control in Primary Care - Prima Trisna Aji; Marta Tania Gabriel Ching Cing; Elinda Rizkasari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Hypertension remains a major global health problem contributing significantly to cardiovascular morbidity and mortality. Poor medication adherence is a key factor leading to uncontrolled blood pressure, particularly in primary care settings. The SMART-HTN pocketbook is a structured educational tool integrating medication adherence, lifestyle modification, and self-monitoring strategies for hypertension management. Objective: This study aimed to evaluate the effectiveness of SMART-HTN pocketbook-based education on medication adherence and blood pressure control among hypertensive patients in primary care. Methods: A quasi-experimental pretest–posttest control group study was conducted involving 60 hypertensive patients (30 intervention and 30 control). The intervention group received structured education using the SMART-HTN pocketbook combined with follow-up reinforcement for eight weeks, while the control group received standard care. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), and blood pressure was assessed using a calibrated digital sphygmomanometer. Data were analyzed using paired and independent t-tests. Results: Baseline characteristics were comparable between groups (p > 0.05). After eight weeks, the intervention group demonstrated a significant increase in medication adherence scores (mean difference = +2.3 points; p < 0.001) compared to the control group. In addition, systolic blood pressure decreased by 13.3 mmHg and diastolic blood pressure decreased by 8.3 mmHg in the intervention group, both significantly greater than the control group (p < 0.001). Conclusion: SMART-HTN pocketbook-based education was associated with improved medication adherence and better blood pressure control among hypertensive patients in primary care. This structured and low-cost intervention shows promise as a scalable strategy for hypertension management in resource-limited settings